2023
DOI: 10.3389/fpsyg.2022.1099331
|View full text |Cite
|
Sign up to set email alerts
|

Emotional framing in online environmental activism: Pairing a Twitter study with an offline experiment

Abstract: As the consequences of anthropogenic climate change become more apparent, social media has become a central tool for environmental activists to raise awareness and to mobilize society. In two studies, we examine how the emotional framing of messages posted by environmental activists influences engagement and behavioral intentions toward environmental action. In the first study, tweets (N = 510k) of 50 environmental activists posted between November 2015 and December 2020 are examined to measure their emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Arlt et al (2018) investigated the effects of media and interpersonal communication on participation in climate discourse online and revealed that receiving information on climate change from social media, including Twitter; active information seeking online; and interpersonal conversations strongly encourage participation [28]. Sanford et al (2023) examined the influence of the emotional framing of messages posted by environmental activists on engagement and behavioral intentions on climate action [29]. Studies related to COVID-19 have included analyses of the impact of a global pandemic on mitigation behavior and information communication on climate change on Twitter [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Arlt et al (2018) investigated the effects of media and interpersonal communication on participation in climate discourse online and revealed that receiving information on climate change from social media, including Twitter; active information seeking online; and interpersonal conversations strongly encourage participation [28]. Sanford et al (2023) examined the influence of the emotional framing of messages posted by environmental activists on engagement and behavioral intentions on climate action [29]. Studies related to COVID-19 have included analyses of the impact of a global pandemic on mitigation behavior and information communication on climate change on Twitter [30][31][32].…”
Section: Introductionmentioning
confidence: 99%